MENINGKATKAN PENGETAHUAN, KETERAMPILAN BERTANI, DAN KEWIRAUSAHAAN GENERASI MUDA MELALUI PELATIHAN HIDROPONIK - Clan, Edward; Sapari, Lili Sarce Joy (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The younger generation, who tend to be adaptive to technology and innovation, sees hydroponics not just as a farming method, but as a profitable and sustainable business opportunity. The implementation techniques include preparation, implementation, and evaluation of the results obtained. This aspect focuses on demonstrating that hydroponics is not just a hobby but also has promising economic potential. Business Opportunities: A special session on entrepreneurship introduced hydroponic business models, market analysis, and how to market the harvest. Participants began to see the potential of hydroponic vegetables as a high-value product. They were given an understanding of the price differences between hydroponic and conventional vegetables in the market.